Nitrous oxide as an effective AFM tip functionalization: a comparative study - Taras Chutora (Beilstein Journal of Nanotechnology, 2019)
We investigate the possibility of functionalizing Au tips by N2O molecules deposited on a Au(111) surface and their further use for imaging with submolecular resolution. First, we characterize the adsorption of the N2O species on Au(111) by means of atomic force microscopy with CO-functionalized tips and density functional theory (DFT) simulations. Subsequently we devise a method of attaching a single N2O to a metal tip apex and benchmark its high-resolution imaging and spectroscopic capabilities using FePc molecules. Our results demonstrate the feasibility of high-resolution imaging. However, we find an inherent asymmetry of the N2O probe-particle adsorption on the tip apex, in contrast to a CO tip reference. These findings are consistent with DFT calculations of the N2O- and CO tip apexes.